Evaluation of the Hip: History and Physical Examination - Byrd, J. W. Thomas (Sports Physical Therapy Section, APTA, 2007)
Examination of a painful hip is fairly concise and reliable at detecting the presence of a hip joint problem. Hip joint disorders often go undetected, leading to the development of secondary disorders. Using a thoughtful approach and methodical examination techniques, most hip joint problems can be detected and a proper treatment strategy can then be implemented based on an accurate diagnosis. The purpose of this clinical commentary is to present a systematic examination process that outlines important components in each of the evaluation areas of history and physical examination (including inspection, measurements, symptom localization, muscle strength, and special tests).